The role of dopamine D2 and neuregulin-1 receptors in schizophrenia relevant phenotypes of cognition, attention and memory - Mathur, Naina (2012)
Aberrant neurotransmitter function promotes cognitive deficits in schizophrenia. These abnormalities in functioning are seen as disruptions in attentional and information processing, as well as disruptions in the consolidation and retrieval of information. Tasks of attentional salience and memory that are used to model these disruptions include the latent inhibition (LI) task of attentional salience, prepulse inhibition (PPI) task of sensorimotor gating and an Episodic memory (EM) task, which is an index of memory for episodes at a particular point in time. Aberrant functioning of candidate genes that are associated with risk for schizophrenia may be seen as behavioural alterations in these tasks of schizophrenia relevant phenotypes. dopaminergic hyperactivity and hypofunction have been implicated in mediating disruptions on these cognitive tasks. Increased transmission in the dopamine system in the striatal region promotes schizophrenia symptoms, and indirect dopamine (DA) agonist Amphetamine worsens these symptoms in patients, and disrupts schizophrenia relevant behaviours on these cognitive tasks. We investigated the effects of deletion of two genes relevant to schizophrenia on cognitive tasks known to be disrupted in the disorder. The effect of deletion of the dopamine D2 receptor (D2R) and trans membrane (TM) domain Neuregulin-1 (Nrg-1) receptor were investigated in mediating disruptions in cognitive processes in an animal model of schizophrenia. The role of the D2R in an attentional model of sensorimotor gating was assessed. PPI was attenuated in D2R knock out (KO), in a one day sensorimotor gating task. In a one day PPI test protocol, amphetamine disruptions on PPI were spared in D2R WT and KO mice. Following on from previous reports of disrupted LI by a single low dose amphetamine injection, separated by 24h interval, we established a single vs. two low dose PPI protocol in order to facilitate a direct comparison of amphetamine induced disruption in LI with PPI. A one injection (prior to test only) vs. two injection (prior to habituation and prior to test) task was established. In the two day protocol, a single low dose of amphetamine disrupted PPI in D2R KO mice and reduced startle reactivity to the 120 dB pulse alone trials. Two low dose injections of amphetamine however, do not disrupt PPI in D2R KO or their WT littermates, and do not mimic low dose amphetamine disruptions in the LI task. These findings demonstrate that prior conclusions about the requirement of the D2R for amphetamine effects in PPI does not generalise to all dose regimens. Episodic memory was also investigated as a measure of cognitive impairment in schizophrenia. D2R KO mice show sex specific dissociations on an EM task. Male D2R WT and KO animals show equal exploration of old vs. recent objects on the what-when component of the EM task, and female KO animals show enhanced memory for old vs. recent objects. Both D2R WT and KO mice show intact memory for displaced objects. These deficits were also investigated in the TM domain Nrg-1 model. Nrg-1 has been implicated as a candidate gene for schizophrenia, and behavioural phenotypes assessing its role in cognitive impairment in schizophrenia were established. Intact LI is seen in both Nrg-1 WT and Het animals. Nrg-1 TM domain Het mutants also show deficits on the schizophrenia relevant PPI task. Nrg-1 Het mutants show attenuated % PPI compared to their WT littermates, which reflects interrupted sensorimotor gating in schizophrenia. Lastly, we found some evidence that reduced function of TM-domain of the Nrg-1 gene disrupted episodic-like memory (what- where-when recognition) in males and improved it in females.